2010
DOI: 10.1007/s10344-010-0375-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fecal age and seasonality on steroid hormone concentration as a reproductive parameter in field studies

Abstract: We studied how fecal age (6, 12, 24, 48, 72, and 168 h) and seasonality affect variation in the fecal steroid hormone metabolite concentration in three endangered mammalian species, Mhorr gazelle, Saharan Barbary sheep, and the Iberian lynx. Except for estrogens, concentrations remained stable for at least 48 h in the Mhorr gazelle and the Saharan Barbary sheep. Steroid hormone metabolite concentration remained stable in the Iberian lynx throughout the experiment (1 week). Seasonality was the main factor affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…In domestic fowl, a delay of up to 24 h between defecation and the freezing of a dropping did not affect faecal levels of oestradiol and testosterone metabolites (Cockrem and Rounce, 1994). Abáigar et al (2010) found similar results for Iberian lynx, where sexual steroid metabolite levels measured in faeces did not change after one week. Studies that aim to address camivore conservation questions may rely on these data, but as faecal bacteria can vary among species, the alterations that affect faecal metabolites may be species-dependent.…”
Section: Discussionsupporting
confidence: 76%
“…In domestic fowl, a delay of up to 24 h between defecation and the freezing of a dropping did not affect faecal levels of oestradiol and testosterone metabolites (Cockrem and Rounce, 1994). Abáigar et al (2010) found similar results for Iberian lynx, where sexual steroid metabolite levels measured in faeces did not change after one week. Studies that aim to address camivore conservation questions may rely on these data, but as faecal bacteria can vary among species, the alterations that affect faecal metabolites may be species-dependent.…”
Section: Discussionsupporting
confidence: 76%
“…less than 30 h between defecation and freezing of the samples). A previous study investigated the stability of steroid metabolites in Iberian lynx ( Lynx pardinus ) fecal samples concluding that those compounds remained stable in feces for at least 1 week under field conditions µAbáigar et al, ]. Even though we did not perform the same assay as the latter study, we extrapolate from those findings to our study and believe there was enough stability of steroid metabolites in the jaguar fecal samples.…”
Section: Discussionmentioning
confidence: 45%
“…The content of steroid metabolites in fecal samples can be altered by several factors, such as bacterial enzyme activity, and environmental humidity and temperature µWinter et al, ; Cerone‐McLernon et al, ; Bokkenheuser et al, ; Abáigar et al, ]. We did not assess stability of the immunoreactive compounds in jaguar fecal samples; however, all samples in our study were frozen while still relatively “fresh” (i.e.…”
Section: Discussionmentioning
confidence: 91%
“…If we could not collect adequate sample sizes of fresh fecal samples on one sampling day, we returned the day after. This sampling scheme ensured that collected samples which were at maximum 24 h old which does not have an effect on hormone levels (Abáigar et al, 2010; Escribano-Ávila et al unpublished results). Fresh samples were collected in plastic tubes and immediately stored in a portable freezer at À20 C. They were then transferred to a conventional freezer in the laboratory and maintained at the same temperature until physiological analyses were conducted (Sheriff et al, 2011).…”
Section: Fecal Sample Collectionmentioning
confidence: 96%